What women want - Goldsmith, Josh.; Yuspa, Cathy; Drake, Diane; Meyers, Nancy; Gibson, Mel.; Hunt, Helen, 1963-; Tomei, Marisa; Feuerstein, Mark.; Holly, Lauren; Alda, Alan, 1936-; Paramount Pictures Corporation; Icon Productions; et al. (Hollywood, Calif. : Paramount, 2001)
A cocky, chauvinistic ad agency exec magically acquires the ability to hear what women are thinking. He puts this to especially good use with his new superior (Hunt), whose job he was in line to get. Then competition turns into romance.
Originally produced as motion picture in 2000.
Special features: 2 theatrical trailers, cast & crew interviews, behind-the-scenes featurette, commentary by director Nancy Meyers & production designer Jon Hutman.
Director of photography, Dean Cundey; music, Alan Silvestri; film editors, Stephen A. Rotter, Thomas J. Nordberg.
Mel Gibson, Helen Hunt, Marisa Tomei, Mark Feuerstein, Lauren Holly, Alan Alda.
Rated PG-13.
DVD; widescreen version.
Keywords: Man-woman relationships -- Drama; Comedy films; Feature films; Video recordings for the hearing impaired